AN ANALYSIS OF SPEECH ACT UTTERED BY DOWN SYNDROME CHARACTER IN PEANUT BUTTER FALCON MOVIE - Fitrah Rahmadani; Sardian Maharani Asnur (CV Swa Anugrah, 2023)
This research discussed about Speech Acts of Down syndrome character which aimed to analyze the types of illocutionary act uttered by Down syndrome character and perlocutionary act performed by the receiver after hearing down syndrome‟s utterances. This research focused on the use of illocutionary acts types of Searle‟s theory and the perlocutionary act of Cutting‟s theory. This research applied decriptive qualitative method in revealing the data. Data of this study were dialogues in the “Peanut Butter Falcon Movie”. The study revealed that the Down syndrome character performed five types of illocutionary acts i.e. declaratives, representatives, expressive, directives, commissives with the result of perlocutionary act which all of the receivers understand the intention in every utterance performed by Down syndrome. The writer identified that representative, directive, expressive were the most dominant performed by down syndrome character. Commissive and declarative were the least performed illocutionary act by down syndrome character. Also, the perlocutionary act performed by the receivers were clear and in a proper way of responding towards down syndrome person. The results of this research are down syndrome person performed their utterances properly according to what he uttered in his sentence along with the grammatical function he used. He delivered his intention properly which made the listeners or the receivers understand the utterances well and provided a proper answer to a down syndrome person. The writer concluded that the receiver responded well to down syndrome‟s utterance because they were understanding well the condition of down syndrome person.